2020
DOI: 10.1159/000511452
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Neovascularization in Nondiabetic Renal Allograft Is Associated with Calcineurin Inhibitor Toxicity

Abstract: <b><i>Introduction:</i></b> Extra efferent arterioles, also known as polar vasculosis (PV), are often observed in the glomerular vascular pole and are associated with glomerular hypertrophy, indicating early recurrent diabetic kidney disease (DKD) in renal allografts. However, its significance in patients without diabetes remains uncertain. <b><i>Methods:</i></b> A total of 9,004 renal allograft biopsy specimens obtained between January 2007 and December 2017 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In the multivariate logistic regression analysis, IFTA was negatively associated with polar vasculosis, whereas subendothelial widening of GBM, glomerulomegaly, glomerular class by the RPS classification ≥IIb, vascular lesions, age, eGFR, and hemoglobin A1c were positively associated with polar vasculosis. Previous several studies have shown the relationships between polar vasculosis and more advanced mesangial expansion, glomerulomegaly, and arteriolar hyalinosis in human DKD, consistent with this study 5 , 6 , 7 , 11 . Notably, this study also found a negative correlation between polar vasculosis and IFTA in addition to previous findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the multivariate logistic regression analysis, IFTA was negatively associated with polar vasculosis, whereas subendothelial widening of GBM, glomerulomegaly, glomerular class by the RPS classification ≥IIb, vascular lesions, age, eGFR, and hemoglobin A1c were positively associated with polar vasculosis. Previous several studies have shown the relationships between polar vasculosis and more advanced mesangial expansion, glomerulomegaly, and arteriolar hyalinosis in human DKD, consistent with this study 5 , 6 , 7 , 11 . Notably, this study also found a negative correlation between polar vasculosis and IFTA in addition to previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Abnormal angiogenesis is involved in the pathogenesis of DKD, and the development of extra vessels, termed polar vasculosis (perihilar neovascularization), is noted as an early kidney lesion in DKD 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 . Although the exact structure of polar vasculosis is currently unknown, a study using reconstruction of three‐dimensional images suggests that these vessels are angiogenesis connecting afferent arterioles, anastomosed glomerular capillaries, efferent arterioles, and peritubular capillaries 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the polar type of PGMVs is observed in hypertensive nephropathy, thrombotic microangiopathy, and calcineurin inhibitor nephrotoxicity in transplanted kidney. 23,24 On the other hand, it is possible that PGMVs may not be present in renal diseases with severe vascular damage, such as antineutrophil cytoplasmic antibody-associated vasculitis presenting with rapidly progressive glomerulonephritis, where good angiogenesis and capillary regeneration cannot be induced and renal biopsy is usually performed in the acute phase of diseases. Glomeruli are constructed by a highly developed and differentiated vascular network.…”
Section: Discussionmentioning
confidence: 99%